2021
DOI: 10.1001/jamanetworkopen.2021.10782
|View full text |Cite
|
Sign up to set email alerts
|

Association of Simulated COVID-19 Vaccination and Nonpharmaceutical Interventions With Infections, Hospitalizations, and Mortality

Abstract: Key Points Question What is the association of COVID-19 vaccine efficacy and coverage scenarios with and without nonpharmaceutical interventions (NPIs) with SARS-CoV-2 infections, hospitalizations, and deaths? Findings A decision analytical model of North Carolina found that removing NPIs while vaccines were distributed resulted in substantial increases in infections, hospitalizations, and deaths. Furthermore, as NPIs were removed, higher vaccination covera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
94
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(96 citation statements)
references
References 47 publications
0
94
0
2
Order By: Relevance
“…Very recently, the intuition that social distancing remains key during vaccination rollout stimulated few studies on the effects of a vaccine on the adoption of NPIs in specific settings [ 46 50 ]. An agent-based model applied to North Carolina showed that lifting NPIs during vaccines distribution would imply a substantial increase in infections and deaths [ 51 ]. Similarly, a data-driven model of SARS-CoV-2 transmission for China estimated that NPIs need to remain in place at least one year after the start of vaccination to avoid a generalized disease resurgence [ 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, the intuition that social distancing remains key during vaccination rollout stimulated few studies on the effects of a vaccine on the adoption of NPIs in specific settings [ 46 50 ]. An agent-based model applied to North Carolina showed that lifting NPIs during vaccines distribution would imply a substantial increase in infections and deaths [ 51 ]. Similarly, a data-driven model of SARS-CoV-2 transmission for China estimated that NPIs need to remain in place at least one year after the start of vaccination to avoid a generalized disease resurgence [ 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even with the expanding uptake of vaccination, non-pharmaceutical interventions will remain critical components of pandemic control [ 24 ]. Therefore, easily accessible, effective testing strategies must be rigorously studied to inform public health policy.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, we should carefully explore a manageable degree of restrictions and their relaxation. The importance of the combination of vaccine rollout and NPIs has been shown in other studies as well [50,51]. We will have to keep bracing for occasional surges of the disease leading to strict measures, such as those under a state of emergency.…”
Section: Discussionmentioning
confidence: 94%